2016
DOI: 10.2459/jcm.0000000000000376
|View full text |Cite
|
Sign up to set email alerts
|

Pathophysiology of cardiotoxicity induced by nonanthracycline chemotherapy

Abstract: The risk and mechanism of chemotherapy-induced cardiotoxicity (CTX) vary depending on the type and intensity of the anticancer regimen. Myriad chemotherapeutic drugs produce adverse cardiovascular effects such as arterial hypertension, heart failure, and thromboembolic events. Among the numerous classes of these drugs, anthracyclines have been studied most extensively because of their overt cardiovascular effects and the high associated incidence of heart failure. However, CTX might also be caused by other typ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
89
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 97 publications
(92 citation statements)
references
References 64 publications
2
89
0
1
Order By: Relevance
“…For example, the alkylating agent cyclophosphamide, used in AML treatment for conditioning in SCT, may cause cardiotoxicity (Madeddu et al, 2016). For example, the alkylating agent cyclophosphamide, used in AML treatment for conditioning in SCT, may cause cardiotoxicity (Madeddu et al, 2016).…”
Section: Tyrosine Kinase Inhibitorsmentioning
confidence: 99%
“…For example, the alkylating agent cyclophosphamide, used in AML treatment for conditioning in SCT, may cause cardiotoxicity (Madeddu et al, 2016). For example, the alkylating agent cyclophosphamide, used in AML treatment for conditioning in SCT, may cause cardiotoxicity (Madeddu et al, 2016).…”
Section: Tyrosine Kinase Inhibitorsmentioning
confidence: 99%
“…Anthracyclines (eg., doxorubicin, epirubicin, daunorubicin, idarubicin) have been extensively studied because of the high incidence of cardiac insufficiency due to cardiotoxicity and significant cardiovascular effects [1,2]. However, cardiotoxicity may also occur with other chemotherapeutic agents including alkylating agents (cyclophosphamide, ifosfamide), platinum agents, antimetabolites (5-fluorouracil, capecitabine), antibiotics (mitoxantrone, mitomycin, bleomycin) and antimicrobial agents (taxanes) [3]. Although cardiotoxicity has been reported by oxidative stress induced by cisplatin-related reactive oxygen metabolites from platinum group chemotherapeutics, fewer studies have been reported on oxaliplatin(OXA) cardiotoxicity [4,5,6].…”
Section: Introductionmentioning
confidence: 99%
“…21 Other potential causes are endothelial damage and transient stress-induced cardiomyopathies, as well as coronary thrombosis and arteritis, leading to manifestations such as asymptomatic EKG changes to acute pulmonary edema, arrhythmias, and myocardial infarctions with ST segment and cardiac biomarker elevations. 22 The risk of cardiotoxicity of 5-FU depends on the route and schedule of administration but is not necessarily dependent on underlying cardiovascular disease. 19 Several studies in animal models have shown that 5-FU administration can lead to depletion of high energy phosphates in both a time and dosing dependent fashion which may be the etiology of angina.…”
Section: Non-anthracyclinesmentioning
confidence: 99%